KILLER IMMUNOGLOBULINE LIKE RECEPTOR GENE ANALYSIS IN CHRONIC LYMPHOCYTIC LEUKEMIA AND ITS RELATION WITH AUTOIMMUNITY - Mustafa Murat Özbalak; Işıl Erdoğan Özünal; Selin Berk; Tuğrul Elverdi; Ayşe Salihoğlu; Ahmet Emre Eşkazan; Ezgi Pınar Özbalak; Muhlis Cem Ar; Şeniz Öngören; Zafer Başlar; Yıldız Aydın; Seda Ekizoğlu; et al. (İstanbul Tıp Fakültesi Dergisi)
Objective: Our study was performed on 49 chronic lymphocytic leukemia (CLL) patients followed in the outpatient clinic of the Istanbul University Cerrahpasa Medical Faculty Department of Hematology. We aimed to analyze the relationship between autoimmune phenomena and CLL. Methods: Twenty-five CLL patients with and 24 CLL patients without autoimmune phenomenon were included. Thirty-two of them were male and 17 were female. No statistically significant difference in the median age at diagnosis (60 vs 64) and in the median follow-up time (59 months vs 71 months) was detected. The initial diagnostic parameters were similar. Results: In our autoimmune phenomenon cohort, the most frequent autoimmune disease was autoimmune hemolytic anemia (AIHA) followed by immune thrombocytopenia (ITP) and pure red cell aplasia (PRCA). The direct antiglobulin positivity at the time of diagnosis was increased in the autoimmune phenomenon group (p=0.024). Additionally, the stage of CLL in patients ofthe autoimmune phenomenon group was more advanced than the other group (p=0.04). Although the number of autoimmune phenomena was not high enough, the CD38 positive cell ratio over 30% in the peripheral blood was more frequent in PRCA group (p=0.008). Conclusion: We could not determine a relationship between autoimmunity in CLL and KIR genotypes. We believe that a new study in a larger cohort with superior technical conditions should be planned to find accurate responses to our study.